A Printed Wireless Triangle‐Wave Generator via a Smartphone. Issue 1 (4th October 2021) - Jung, Younsu; Shrestha, Sagar; Lim, Namsoo; Park, Hyejin; Sun, Junfeng; Park, Jinhwa; Parajuli, Sajjan; Shrestha, Kiran; Kim, Seongryeong; Cho, Gyoujin
Abstract : An all‐printed wireless triangle‐wave generator is needed to produce a printed wireless and disposable cyclic voltammetry (CV)‐based biosensor to detect redox‐active analytes. The generator should produce positive and negative potentials from the smartphone's near‐field‐communication (NFC) (13.56 MHz) carrier signal. However, the printed triangle‐wave generator that contains rectenna and a ring oscillator fails to wirelessly operate with a smartphone because the polarized (±) DC power from the NFC carrier signal of the smartphone could not be provided through the utilization of a printed Schottky diode. Herein, an n‐type indium gallium zinc oxide (IGZO)‐based ink is formulated to print the Schottky junction with a high work function of the printed electrode provided by in situ doping of printed poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) on Ag electrode. The printed IGZO‐based rectenna could wirelessly harvest polarized (±) DC 10 V from the smartphone to generate a triangle wave with positive and negative potentials through the printed ring oscillator. Abstract : Using the gravure printing process, all‐printed indium gallium zinc oxide (IGZO)‐based Schottky diodes are obtained that show a turn‐on voltage of 0.6 V and an on‐current of 0.8 mA/cm −2 . The resulting printed Schottky diode uses two voltage triplers on the rectenna to generate a polarized DC ± 10 V from a smartphone's near‐filed‐communication (NFC) carrier.